DETECTION OF COMMON BACTERIAL AND VIRAL PATHOGENS CAUSING COMMUNITY ACQUIRED PNEUMONIA USING RT-PCR AND ITS CORRELATION WITH SOME CLINICAL AND DEMOGRAPHIC PARAMETERS - HABEEB , LORNA AMER; SAEED, ALI YAHYA (Journal of Duhok University, 2023)
Background: Pneumonia is the most serious infectious disease and one of the most common causes of death in the world. It clinically divided into community-acquired pneumonia (CAP) and nosocomial pneumonia. Pneumonia can be caused by bacteria, viruses, fungi and protozoa. Although culture considered as standard gold method for diagnosis of bacterial causes of pneumonia but still characterized by low sensitivity and time consuming. Because data concerning etiology of CAP are limited in our area. The aim of the study was to detect common bacterial and viral causes of CAP using multiplex real time PCR technique as well as to study their association with demographic and clinical characteristics. Methods: A total of 50 sputum samples were collected from hospitalized community acquired pneumonic adult patients aging from 18 to more than 65 years old in Azadi teaching and emergency hospitals in Duhok city from a period of from June 2022 to June 2023. Bosphore RPP Basic Bundle Kit of RT-PCR (Anatolia, Turkey) was used. Results: From 50 samples, 42 (84%) were positive by RT-PCR technique. The most predominant detected pathogens were Streptococcus pneumoniae 23 (46%) followed by Klebsiella pneumoniae 14 (28%), Staphylococcus aureus 3 (6%), Mycoplasma pneumonia and Legionella pneumophila with similar results 1(2%), while Moraxella catarrhalis, Bordetella pertussis, Pneumocytis jirovecii, Legionella pneumophila /longbeachae, Haemophilus influenzae type b and Chlamydia pneumoniae were negative. All samples were negative for Influenza B, Adenovirus, Parechovirus and Influenza C viruses. Conclusion:From the results of this study, it can be concluded that among bacterial causes of adult CAP patients, Streptococcus pneumoniae was the predominant followed by Klebsiella pneumoniae, while among atypical bacteria both Mycoplasma pneumoniae and Legionella pneumophilia were detected. All samples were negative for Adenovirus, Influenza B, C and Parechovirus. CAP was more commonly found among young aged adult, males, patients with comorbidities and with CURB-65 score-2.